Iliopsoas abscess: A clinical dilemma — case report - Ng We Yong, Yuki Julius; Ikbaal, Muhammad (Journal of Surgery and Medicine, 2022)
Iliopsoas abscess (IPA) is the accumulation of pus inside the iliopsoas muscle compartment. The early stages of its clinical presentation are often non-specific and therefore incidentally diagnosed with computed tomography. We describe the case of a 27-year-old man with a history of Crohn’s disease presenting with right-sided lower back pain radiating downwards to the lateral part of his thigh and exacerbated with hip movement. Examination of the patient showed a cachectic physique with a fixed flexion deformity at the right hip with a positive psoas sign. We further report the clinical dilemma on the diagnosis between Crohn’s disease and intestinal tuberculosis and the subsequent management of IPA secondary to Crohn’s disease. Our patient was managed with a loop ileostomy for bowel rest with continuous abscess draining and discharged after 3 months. After the reversal of ileostomy, the patient was satisfied with the overall outcomes. The clinical dilemma stems from the rising incidence of Crohn’s disease in Malaysia, as the clinical presentation of intestinal tuberculosis and Crohn’s disease is similar. Therefore, it is important for countries transitioning to higher income groups to be able to suspect and treat the condition accordingly.